2016
DOI: 10.1007/s10103-016-1946-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy stimulates tissue repair and reduces the extracellular matrix degradation in rats with induced arthritis in the temporomandibular joint

Abstract: The objective of this study was to characterize morphological and biochemistry action of low-level laser therapy (LLLT) on induced arthritis in the temporomandibular joint (TMJ) of rats. Twenty-four male Wistar rats were randomly divided into groups with 12 animals each: (AG) group with arthritis induced in the left TMJ and (LG) group with arthritis induced in the left TMJ and treated with LLLT (830 nm, 30 mW, 3 J/cm(2)). Right TMJs in the AG group were used as noninjected control group (CG). Arthritis was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 44 publications
5
19
0
5
Order By: Relevance
“…Therefore, MMP-13 may be considered a critical component of the cellular machinery involved in regulating articular cartilage turnover and a potential therapeutic target for cartilage destruction [68]. Several studies have reported the effect of low-level laser irradiation on MMP synthesis and associated pathological conditions [66,[72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MMP-13 may be considered a critical component of the cellular machinery involved in regulating articular cartilage turnover and a potential therapeutic target for cartilage destruction [68]. Several studies have reported the effect of low-level laser irradiation on MMP synthesis and associated pathological conditions [66,[72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…In one rat model of osteoarthritis, laser therapy caused a reduction in neutrophil migration, oxidative stress, altered levels of cyclooxygenase-2 and other proinflammatory mediators [24]. Another demonstrated that LLLT stimulates tissue repair and reduces the rate of extracellular matrix degradation [25]. There is also some evidence that LLLT promotes fibroblast proliferation, collagen synthesis and bone regeneration [26][27][28][29][30][31].…”
Section: Laser Therapymentioning
confidence: 99%
“…Em nosso trabalho, foi observada reversão total do limiar nociceptivo dos animais tratados com laser, a partir da primeira sessão no grupo operado mais laser, e a partir da segunda sessão no grupo falso operado mais laser, e se manteve até a décima sessão analisada, sugerindo a efetividade da LLLT na diminuição da nocicepção, provavelmente pela redução do processo inflamatório intra-articular. Muito provável que ocorra também a efetividade do laser na diminuição do grau de edema, pois quanto mais intenso for, maior será a sentitização central dos neurônios periféricos em resposta a inflamação periférica (Barretto et al, 2013).Também, outro estudo experimental para análise o efeito da LLLT na artrite da ATM por indução com CFA, verificou a diminuição do processo inflamatório crônico, a melhora na reparação, a modulação na atividade de enzimas que agem no remodelamento da matriz tecidual, havendo diminuição na espessura do disco articular (Lemos et al, 2016). Sabe-se que a inibição da síntese de prostaglandinas induzida pela LLLT promove o aumento da proliferação celular endotelial (Moore et al, 2005).…”
Section: Discussionunclassified
“…Em seu trabalho os mesmos autores avaliaram a relação dessa lesão com o crescimento mandibular, encontrando diferenças significantes entre os lados (Toledo etal., 2014). Outros modelos são utilizados para o estudo da inflamação ou da nocicepção na ATM,representados pela injeção de substancias flogisticas, como formalina (Goulartet al, 2005;Barretto et al, 2013), carragenina (Goulart et al, 2005;Carvalho et al,2011;Barretto et al, 2013),CFA na articulação (Lemos et al, 2016;Hutchins et al,2000) ou, ainda,óleo de mostarda (Bonjardim et al, 2009). O CFA tem sido utilizado também em modelos de dor inflamatória (Chacur et al,2009).No caso deste trabalho, o uso do modelo físico de dor por lesão no disco da ATM seria mais próximo da realidade, pois ao nosso ver, mimetiza a situação clínica de dor da ATM acometida nos pacientes por problemas intra-articulares, se comparado com os modelos que utilizam soluções medicamentosas ou compostos irritativos.…”
Section: Discussionunclassified
See 1 more Smart Citation